2020
DOI: 10.1182/blood.2019002329
|View full text |Cite
|
Sign up to set email alerts
|

Fc-modified HIT-like monoclonal antibody as a novel treatment for sepsis

Abstract: Sepsis is characterized by multiorgan system dysfunction that occurs because of infection. It is associated with high morbidity and mortality and is in need of improved therapeutic interventions. Neutrophils play a crucial role in sepsis, releasing neutrophil extracellular traps (NETs) composed of DNA complexed with histones and toxic antimicrobial proteins that ensnare pathogens, but also damage host tissues. At presentation, patients often have a significant NET burden contributing to the multiorgan damage. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
93
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(100 citation statements)
references
References 86 publications
3
93
0
2
Order By: Relevance
“…In addition, in several observational studies, administration of antiplatelet therapy has been shown to be associated with improved outcome in patients with sepsis (Eisen et al, 2012;Chen et al, 2015). Recently, a novel treatment which stabilizes NETs to enhance their capacity of capturing bacteria and prevent the release of antibacterial compounds causing tissue damage has been discovered (Gollomp et al, 2020). Researchers developed an antibody that binds to complexes of NETs and platelet factor 4 (PF4), a protein released by activated platelets, which causes the NETs to resist degradation and improves their ability to capture bacteria.…”
Section: Potential Therapeutic Strategy Targeting Neutrophils For Sepsis Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, in several observational studies, administration of antiplatelet therapy has been shown to be associated with improved outcome in patients with sepsis (Eisen et al, 2012;Chen et al, 2015). Recently, a novel treatment which stabilizes NETs to enhance their capacity of capturing bacteria and prevent the release of antibacterial compounds causing tissue damage has been discovered (Gollomp et al, 2020). Researchers developed an antibody that binds to complexes of NETs and platelet factor 4 (PF4), a protein released by activated platelets, which causes the NETs to resist degradation and improves their ability to capture bacteria.…”
Section: Potential Therapeutic Strategy Targeting Neutrophils For Sepsis Treatmentmentioning
confidence: 99%
“…Neutrophil extracellular traps (NETs) in sepsis are also not controlled properly, and play an important role in tissue damage and coagulation disturbance. combined with antibiotics, this treatment significantly reduced the severity of illness, decreased the levels of bacteria circulating in the blood, and improved survival in the animal sepsis model (Gollomp et al, 2020). A large-scale clinical trial which evaluates the efficacy of antiplatelet therapy in sepsis is currently underway and may provide interesting results in the future (Eisen et al, 2017; Table 1).…”
Section: Potential Therapeutic Strategy Targeting Neutrophils For Sepsis Treatmentmentioning
confidence: 99%
“…In addition, in the murine model it has been shown that binding of a monoclonal antibody to NET complexes in sepsis increases the overall survival. This seems mainly due to the fact that antibody binding protects NETs from DNase I, resulting in less toxic NET-associated degradation products [ 138 ].…”
Section: Net-associated Diseasesmentioning
confidence: 99%
“…However, a more nuanced view of NETs requires an acknowledgement of their beneficial antimicrobial properties. Studies investigating NET stability offer insight into balancing the beneficial and toxic effects of NETs in vivo (80). Platelet factor 4 (PF4), a platelet-associated chemokine, binds, compacts, and stabilizes NETs in the microvasculature, increasing their resistance to DNase I. PF4 increased NET-mediated bacterial capture, reduced the release of NET degradation products, and improved outcomes in murine sepsis (80).…”
Section: Neutrophil Extracellular Traps (Nets)mentioning
confidence: 99%